Enhancing organizational commitment through shared leadership: insights from Saudi higher education - Alghamdi, Atiyah A. (Frontiers in Education, 2024)
This study investigates the impact of shared leadership (SL) on the various dimensions of organizational commitment (OC) within Saudi higher education institutions (HEIs). Employing a descriptive cross-sectional survey design, data were collected from faculty members at a prominent Saudi university using structured questionnaires. The questionnaires included validated scales for SL, encompassing dimensions such as Development and Mentoring, Problem-Solving, Support and Consideration, and Planning and Organizing, as well as for OC, which measured affective, normative, and continuance commitment. Descriptive statistics, correlation, and regression analyses were used to assess the relationships between SL and OC components. The findings indicate that shared leadership is widely practiced, with Development and Mentoring emerging as the most prominent SL dimension. A significant positive relationship was identified between SL and all three OC components, with affective commitment demonstrating the strongest correlation. Additionally, SL was found to significantly predict overall OC, underscoring its role in enhancing faculty commitment. These results highlight the potential of adopting shared leadership practices in HEIs to strengthen faculty engagement and institutional performance. Future research should expand data collection across multiple institutions and examine the combined influence of SL and OC on the quality of education and institutional success.